Poverty and Discrimination - Lang, Kevin (Book collections on Project MUSE., 2011)
Many ideas about poverty and discrimination are nothing more than politically driven assertions unsupported by evidence. And even politically neutral studies that do try to assess evidence are often simply unreliable. In Poverty and Discrimination, economist Kevin Lang cuts through the vast literature on poverty and discrimination to determine what we actually know and how we know it. Using rigorous statistical analysis and economic thinking to judge what the best research is and which theories match the evidence, this book clears the ground for students, social scientists, and policymakers wh.